2008
DOI: 10.1080/07373930701831382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superheated Steam Processing on the Textural and Physical Properties of Asian Noodles

Abstract: Asian noodles were simultaneously cooked and dried in superheated steam at temperatures from 110 to 150 C and steam velocities of 0.5, 1.0, and 1.5 m/s. Textural and key physical properties of color, breaking stress, and starch gelatinization were measured to ascertain the effects of the superheated steam processing. Textural properties of adhesiveness, springiness, cohesiveness, chewiness, resilience, and hardness determined from a TPA were found to be generally unaffected by steam velocity. All properties bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…It is assumed that on continuous heat processing lead to loss of water (90-92%) from the noodles, and as water content is responsible for softness of product, increase of steaming and drying time obviously results in harder product. These results are supported by study of Pronyk et al (2008) who reported that with the increase in processing time firmness or hardness of noodles increases. Sofos et al (1995) studied cohesion and hardness of extrusion-cooked mechanically and hand deboned poultry meat with soy protein isolate and kappa-carrageenan and concluded that with the increase of meat level hardness of extruded product increases.…”
Section: Hardness (N) Of Raw Noodlessupporting
confidence: 81%
See 3 more Smart Citations
“…It is assumed that on continuous heat processing lead to loss of water (90-92%) from the noodles, and as water content is responsible for softness of product, increase of steaming and drying time obviously results in harder product. These results are supported by study of Pronyk et al (2008) who reported that with the increase in processing time firmness or hardness of noodles increases. Sofos et al (1995) studied cohesion and hardness of extrusion-cooked mechanically and hand deboned poultry meat with soy protein isolate and kappa-carrageenan and concluded that with the increase of meat level hardness of extruded product increases.…”
Section: Hardness (N) Of Raw Noodlessupporting
confidence: 81%
“…The ΔE value was increased in chicken noodles with the increase in meat level because of myoglobin content in meat which resulted in increase of avalue (redness) thereby ΔE value. Pronyk et al (2008) reported that with the increase in steaming time all the colour coordinates (L, a-and b-values) decreased significantly. Similar results observed by Wang et al (2013) in thermally treated fish and starch gel where all color coordinates decreases due to starch gelatinization in the starch and mixed gel chips.…”
Section: Hardness (N) Of Raw Noodlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The wheat was milled at the Canadian International Grains Institute (CIGI) in Winnipeg, Manitoba, Canada following standard procedures for the production of straight-grade (75.2% extraction) noodle flour. [14] The flour had a protein content of 13.3% (14.1% moisture content, wet basis) and was used in the preparation of raw alkaline noodles.…”
Section: Methods and Materials Flourmentioning
confidence: 99%